Pengaruh Karakteristik Personal Auditor terhadap Tingkat Penerimaan Penyimpangan Perilaku Dalam Audit - Erni Suryandari (Universitas Muhammadiyah Yogyakarta, Indonesia, 2007)
The role of external auditor opinion is vital in ensuring the proper production of financial report. However, cases of dysfunctional audit behavior has adversely affect the credibility of external auditors opinion. Among the contributing factors to such dysfunctional audit behavior is the personal characteristic of the auditor. The research seek to analyze the relationship between auditors’ individual characteristic and their acceptance to dysfunctional audit behavior. The data is collected from 108 auditors working in audit firms located in Yogyakarta, Surakarta and Semarang. The methodology used is structural equation modeling as it facilitates the use of manifest and latent variables as well as accommodating the existence of inter-relationship among independent variables. The study show that the level of auditor’s locus of control, turnover intention and self esteem in relations to ambitions has significant positive relationships with the level of acceptance of dysfunctional audit behavior, while the self-rated auditor performance have significant negative relationships with the level of acceptance of dysfunctional audit behavior.